Comparative Evaluation of Root Canal Working Length Determination with Three Methods: Conventional Radiography, Digital Radiography and Raypex6 Apex Locator: An Experimental Study - Seyed Amir Mousavi; Amirali Zahedinejad; Behzad Kowsari; Erfan Kolahdouzan; Seyed Iman Mousavi; Sadegh Saeidian (Mashhad University of Medical Sciences, 2021)
Introduction: Determining working length had always been one of the most crucial factors in evaluating prognosis. Radiography as a gold standard way nowadays has some flaws like making a 3D object, image distortion, not measuring the exact location of apical foramen, and putting the patient in a direct X-ray exposure. Here, we compare these three ways in measuring working length of single canal teeth that are narrow. Methods: Initially thirty single canal teeth with narrow canals were selected. After preparing the access cavity, the teeth were mounted in alginate for measuring working length with an apex locator. After that, they mounted in chalk in order to determine the working length using conventional and digital radiographs. Finally, the teeth were removed from the mount and the exact working length assessed using a hand file to compare with the three mentioned methods. Results: This study showed that the mean measured working length of root canal therapy had a significant difference between the four methods (P=0.003). Bonferroni post hoc test showed that the mean exact working length of root canal therapy was significantly lower than measured working length of root canal therapy by conventional radiography (P=0.002), digital radiography (P=0.001) and Raypex6 apex locator (P=0.01). However, there was no significant difference between these three methods (P>0.05). Conclusion: The results of this study showed that the mean measured working length of root canal therapy had no significant difference between digital radiography, conventional radiography, and Raypex6 apex locator but these three methods had a significant difference with the exact teeth length